An Empirical Study on the Factors Affecting Online Shopping Behavior of Millennial Consumers. Issue 3 (3rd July 2017) - SivaKumar, ArunKumar; Gunasekaran, Abirami
ABSTRACT: The online market in India is growing at an exponential rate, predominantly driven by the massive and extensive promotional activities. This strategy may not be appreciable in the long run, hence a real value addition is essential, which is explored through this study. The main objective of this research is to study about the determinants that are affecting the online purchasing behavior of millennial consumers. Conceptual framework, which consists of four factors that may induce online purchase behavior among millennial consumers: consumer innovativeness, perceived benefits, perceived risks, attitude and intention. The population of the study is from the millennial customer's segment of Chennai metro, Tamil Nadu, India, and the study used systematic random sampling. The statistical tools applied are chi-square, ANOVA, correlation, multiple regression, and factor analysis. From the outcomes of this study, factors influencing online purchase are analyzed, and suggestive strategies for online companies are recommended.